Competency assessment of the integrated science process skills and creative thinking abilities of the college freshmen of the University of Nueva Caceres - Fullante, Armin A. (Animo Repository, 1998)
This study is a competency assessment of the integrated science process skills and creative thinking abilities of the college freshmen of the University of Nueva Caceres, SY 1997-1998.The research is a descriptive-correlational study which attempted to establish the relationship between the students' knowledge in the integrated science process skills and creative thinking abilities and some selected student variables through standardized tests and a researcher-made questionnaire.To gather the needed data, three instruments were used, namely: Integrated Science Process Skills Test, Creative Personality Inventory and a researcher-made questionnaire. The statistical techniques used were descriptive statistics, Pearson-product correlation, one-way and two-way ANOVA and stepwise regression.Results of the study indicate that college freshmen tend to be most competent in identifying variables and least competent in operationally defining variables. College freshmen who are graduates of private high school perform better in the different integrated science process skills categories compared with the graduates of public high school. More creative students would obtain higher scores in the Integrated Science Process Skills Test compared with the less creative ones. Grade in Science IV can significantly correlate with the score obtained in the Integrated Science Process Skills Test. No interaction effect can be found between the type of high school enrolled in and the degree of creative abilities of the college freshmen. Thirty percent of the variation could be attributed to students Grade in Science IV. The following recommendations were given: 1) Science teachers should put greater emphasis on the teaching of science processes which can be done by introducing hands-on activities in science classes. 2) Enrichment activities in science classes to improve the science process skills of students. 3) Science teaching should provide opportunities for the development of creativity in problem solving, experimentation and model building. 4) Schools, particularly public high schools, should be provided with the needed science equipment and apparatus as aid in the effective learning of science processes. 5) Science teachers should be trained on the proper handling and use of the laboratory equipment and apparatus. 6) Mental ability as an independent variable which can affect the students' competency in the integrated science process skills could be investigated for further studies. 7) Further research on other factors that may correlate with the students' competency in the integrated science process skills should be further explored.